ANALISIS PERMINTAAN TENAGA KERJA PADA USAHATANI KOPI (Studi Kasus Di Desa Kepala Curup Kecamatan Padang Ulak Tanding Kabupaten Rejang Lebong) - Sriyoto, Sriyoto; Utama, Satria Putra; antony, . (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2004)
The hypothesis of the study were capital, coffee price, labor wages, and price of fertifizers significantfy influence demand for labor in coffee estate management at Padang Ulak Tanding sub district, Rejang Lebong regency. The cobb-douglas model was used for elaborating the objectives. The results significantly show that demand for labor was influenced by capital, labor wages; price of coffee in nurse ring while price of fertilizers was not In the planting, capital and price of fertilizers were influence the demand for labor while labor wages and price of coffee were not. Capital and labor wages significantly influenced the demand for labor while price of coffee and fertilizers were not in the maintaining activities. Price of coffee and capital influence the demand for labor but labor wages and price of fertilizers are not. Government has had to serious attention in terms of technical and management assistances through special programs in improving the best production and productivity.